RELIGIOUS BELIEFS, INGREDIENT SAFETY, HALAL LOGO, AND PROMOTION IMPACT ON GEN Z’S PURCHASE INTENTION FOR WARDAH - Angelica, Angelica; Christanto, Budi (ULTIMA Management, 2025)
Abstract- Generation Z represents a promising market segment with distinct preferences for cosmetic products. This study examines the impact of Religious Belief, Ingredient Safety, Halal Logo, and Promotion on the Purchase Intention of Wardah Halal Cosmetics among Generation Z. A quantitative approach with a causal research design was employed, involving 303 Muslim Generation Z women in the Jabodetabek area. Data were analyzed using multiple linear regression, including validity and reliability tests, classical assumption tests, regression equations, coefficient of determination tests, and significance tests (t-test) using IBM SPSS 27. Findings indicate that Ingredient Safety, Halal Logo, and Promotion significantly influence Purchase Intention, whereas Religious Belief does not have a significant effect. Future research should explore alternative variables and broader perspectives on halal cosmetics to enhance theoretical understanding. In conclusion, Wardah's success in attracting Gen Z consumers lies in its product safety, clear halal certification, and effective promotional strategies rather than relying solely on religious alignment. Keywords: Religious Beliefs; Ingredient Safety; Halal Logo; Promotion; Purchase Intention; Generation Z